PeRiOperative Glucose PRAgMatic (PROGRAM) trial protocol and statistical analysis plan for comparing automated intraoperative reminders to standardise insulin administration in surgical patients at high risk of hyperglycaemia - Karen McCarthy; Robert E Freundlich; Matthew D McEvoy; Matthew S Shotwell; Svetlana Eden; Miklos D Kertai; Jonathan P Wanderer; Matthew Zapf; Dev Patel; Patrick Henson; Eunice Huang; Leslie Fowler (BMJ Open, 2023)
Introduction Studies finding perioperative hyperglycaemia is associated with adverse patient outcomes in surgical procedures spurred the development of blood glucose guidelines at many institutions. In this trial, we will assess the implementation of a clinical decision support tool that is integrated into the intraoperative portion of our electronic health record and provides real-time best practice recommendations for intraoperative insulin dosing in surgical patients at high risk for hyperglycaemia.Methods and design We will assess this intervention using a sequential and repeated cross-over design at the institutional level with periods of time for wash-out, control and study intervention. The unit of analysis will be the surgical case. The primary outcome will be the frequency of hyperglycaemia (>180 mg/dL (10 mmol/L)) at first postoperative anaesthesia care unit measurement. There are several prespecified secondary analyses focused on perioperative glycaemic control.Discussion This protocol and statistical analysis plan describes the methodology, primary and secondary analyses. The PeRiOperative Glucose PRAgMatic (PROGRAM) trial was approved by the Vanderbilt University Institutional Review Board (IRB), Vanderbilt University Medical Center, Nashville, Tennessee, USA (IRB, 220991). The study results will be disseminated via publication in a peer-reviewed journal and presented at national scientific conferences. The results of PROGRAM trial will inform best practice for perioperative standardised insulin administration in surgical patients at high risk of hyperglycaemia.Trial registration number NCT05426096.